Use of Postpartum Hemorrhage Checklist during Vaginal Deliveries: A Quality Improvement Study - Bruce, Katharine E.; Desai, Shivani; Reilly, Kelly; Keil, Arianna; Swanson, Michelle; Cobb, Benjamin; Zahn, Katelin; McKenzie, Christine; Coviello, Elizabeth; Mallampati, Divya; Tully, Kristin P.; Kolarczyk, Lavinia; Maaske, Shannon; Quist-Nelson, Johanna (American Journal of Perinatology, 2024)
Objective Postpartum hemorrhage (PPH) protocols improve patient safety and reduce utilization of blood products; however, few data exist on sustainability of PPH checklist use, how use affects care delivery, and variation of use among patient subgroups. This study aimed to (1) examine compliance with PPH checklist use during vaginal deliveries, (2) evaluate whether checklist use varied by patient and/or care team characteristics, and (3) evaluate whether checklist use was associated with increased use of recommended medications/interventions.Study Design This was a quality improvement study performed from April 2021 through June 2023. A multidisciplinary team developed a revised PPH checklist and used quality improvement methodology to increase checklist use following vaginal birth. Data were collected from medical records and clinician survey. Control charts were generated to track checklist use and evaluate special cause variation. Chi-square tests and logistic regression were used to evaluate variation in medications/interventions and across subgroups.Results During the study period, there were 342 cases of PPH at the time of vaginal birth. The checklist was used in 67% of PPH cases during the 20-month period after implementation in a setting where no checklist was previously being used. We found no statistically significant differences in checklist use by patient or health care team characteristics. Use of tranexamic acid, carboprost, and misoprostol were significantly associated with checklist use.Conclusion This study demonstrated successful implementation of a checklist protocol where no checklist was previously being used, with sustained use in an average of 67% of PPH cases over 20 months. Checklist use was consistent across subgroups and was associated with higher use of interventions shown to lower blood loss.Key Points
Keywords: health care quality improvement; obstetrics and gynecology; patient safety; checklists; postpartum hemorrhage